Mediatory effects of psychological empowerment and self-regulation on the relationships between leadership styles, self-efficacy and structural empowerment with job performance - Shamsifar, Maryam; Veiskarami, Hasanali; Sadeghi, Masoud; Ghazanfari, Firoozeh (Social Determinants of Health, 2019)
Background: This study aimed at designing and testing a model of indirect relationship between leadership styles, self-efficacy, structural empowerment and job performance with the mediation of psychological empowerment and self-regulation among teachers in Khoramabad city. Methods: The study was a correlation research via structural equations modeling. Population of the study were selected from high school teachers in Khoramabad city. We applied these questionnaires: Misha-Spreitzer psychological empowerment; Kappa Aydin et al self-regulatory; Patterson job performance; Blanchard-Hersey leadership styles; Kordnaij, Bakhshizadeh and Fathollahi structural empowerment; Woolfok and Shanen-Moran self-efficacy. Results: Participants in this study were 202 (52.5%) females and 183 (47.5%) males. In regard to education, 6 (1.6%) participants had diploma degree; 36 (9.4%) participants had above diploma degree; 251 (65.2%) participants had bachelor degree; 91 (23.6%) participants had master´s degree and 1 (0.3%) participant had a doctorate degree. The results of data analysis including 385 questionnaires completed by participants with Smart PLS (Partial Least Squares) software showed that model fits with data. Justifying and participatory leadership styles as well as structural empowerment had causal and indirect effects on job performance with mediation of psychological empowerment. Psychological empowerment and self-regulatory mediate the relationships between justifying leadership style and job performance; structural empowerment and job performance as well as self-efficacy with job performance. Conclusion: Improving self-efficacy of teachers and structural empowerment helps to have self-regulating teachers with higher psychological empowerment. Self-regulation and self-efficacy and change in leadership style lead to structural empowerment in schools.